Second Primary Malignancies in Adults with Gastric Cancer – A US Population-Based Study - Shah, Binay Kumar; Khanal, Amit; Hewett, Yvonne (Frontiers in Oncology, 2016)
Background: Multiple studies have examined the incidence of secondary primary malignancies (SPM) in gastric cancer patients in Europe and Asia. This retrospective review was conducted to analyze risk of SPM in patients with gastric cancer diagnosed in the United States (US). Methods: We included adult patients diagnosed with gastric cancer from the Surveillance, Epidemiology and End Result (SEER) 13 database. We calculated the risk of secondary primary malignancies in these patients using the multiple primary standardized incidence ratio (MP-SIR) session of SEER*stat software and performed subset analyses of SPM with regard to age, sex, radiotherapy used, and latency period. Results: Among 33,720 patients, 1838 (5.45%) developed 2019 secondary primary malignancies with an observed/expected (O/E) ratio of 1.11 (95% confidence interval (CI) = 1.06-1.16, p<.001) and an absolute excess risk (AER) of 18.16 per 10,000 population. The median time to first SPM from the time of diagnosis of gastric cancer was 46.9 months (range 6-239 months). Significant excess risk was observed for gastrointestinal malignancies [O/E ratio 1.71 (CI = 1.59-1.84, p<.001)], thyroid [O/E ratio 2.00 (CI = 1.37-2.8, p<.001)] and pancreatic cancer [O/E ratio 1.60 (CI = 1.29-21.96, p<.001)]. Risk of secondary melanoma, breast cancer and prostate cancer was lower than in the general population. Conclusions: The risk for secondary primary malignancies is significantly increased in adults with gastric cancer compared to the general population.